Equity impact of a choice reform and change in reimbursement system in primary care in Stockholm County Council. Issue 1 (June 2015) - Agerholm, Janne; Bruce, Daniel; Ponce de Leon, Antonio; Burström, Bo
Abstract Background In 2008 reforms were introduced in primary care in Stockholm County Council to increase patient choice. These reforms included changes to the reimbursement system from one that was primarily based on need-weighted capitation system (75 %) to a system largely based on fee-for-service (60 %) and freedom of establishment of primary care clinics. The new reimbursement system created incentives for producing many visits and additional primary care clinics were established, particularly in areas that were already well served. This study analyses if and how the choice reform and change of reimbursement system has affected equity in primary care consumption by investigating whether the increase in visits reflects levels of need and to what extent the reform have affected equity in health care between areas. Methods Cross-sectional data from the public health survey in Stockholm County 2006 (n = 34, 707) and 2010 (n = 30, 767) were linked to individual register data on socio-demographic characteristics and health care utilization in 2007 and 2011. Information on self-reported health status and disability pension was used as indicators of need of health care. Negative binomial regression was used to analyse the differences in GP visits between the two years. Results The total number of visits to GPs increased by 46 % from 2007 to 2011 and the proportion visiting a GP increased by 17 %. Both men and women reporting poor mental health and women with limiting longstanding illness and poor self-rated health had significantly smaller increase in number of visits than healthy women and men. Men with poor health status living in disadvantaged areas had a smaller increase than men with poor health status living in other areas of Stockholm County. Conclusions The reform did not particularly benefit those with greater health care needs, and there are indications of a negative impact on equity in primary care after the introduction of the reform. There were signs of a lesser increase in total number of visits to GPs among those with poor mental health, among women with poor self-rated health and limiting longstanding illness, and among men living in disadvantaged areas.